2016
DOI: 10.1007/s11306-016-1050-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum metabolomics for early diagnosis of esophageal squamous cell carcinoma by UHPLC-QTOF/MS

Abstract: Introduction Previous metabolomics studies have revealed perturbed metabolic signatures in esophageal squamous cell carcinoma (ESCC) patients, however, most of these studies included mainly late-staged ESCC patients due to the difficulties of collecting the early-staged samples from asymptotic ESCC subjects. Objectives This study aims to explore the early-staged ESCC metabolic signatures and potential of serum metabolomics to diagnose ESCC at early stages. Methods Serum samples of 97 ESCC patients (stage 0, 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
121
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(122 citation statements)
references
References 49 publications
1
121
0
Order By: Relevance
“…This pathway, which contains both LA and ALA, is vital for normal physiological function, cellular function and signaling, and the immune response [36]. A series of studies has shown that dysregulation of LA metabolism takes place in a variety of malignant diseases [17,24,37]. However, the separate roles of the LA and ALA in ESCC risk remain unclear and our understanding of them incomplete.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pathway, which contains both LA and ALA, is vital for normal physiological function, cellular function and signaling, and the immune response [36]. A series of studies has shown that dysregulation of LA metabolism takes place in a variety of malignant diseases [17,24,37]. However, the separate roles of the LA and ALA in ESCC risk remain unclear and our understanding of them incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…Mayerle et al [16] recruited patients for a large-scale study to differentiate pancreatic ductal adenocarcinoma from chronic pancreatitis, achieving high accuracy. In order to elucidate the mechanisms of ESCC onset and discover novel biomarkers, Wang et al [17] analyzed a relatively large number of early-stage ESCCs by serum LC-MS-based metabolomics. Moreover, Xu et al [18] discovered a series of potential biomarkers for ESCC diagnostic and therapeutic purposes.…”
Section: Introductionmentioning
confidence: 99%
“…All studies were Phase I biomarker discovery studies. Of the 30 included studies, 18 were from Asia and the Far East [8,9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], seven from Europe [27][28][29][30][31][32][33], three from North America [34][35][36], and two from the Middle East [37,38]. ASCC tumour sites identified were the head and neck (n = 17), oesophageal (n = 8), and lung (n = 5).…”
Section: Resultsmentioning
confidence: 99%
“…LC‐MS/MS analyses (Wang et al . ) were performed using an UHPLC system (1290; Agilent Technologies, Palo Alto, CA, USA) with a UPLC HSS T3 column (1·7 μ m × 2·1 mm × 100 mm; Waters, Milford, MA, USA) coupled to Q Exactive (Orbitrap MS; Thermo, Waltham, MA, USA). MS raw data (.d) files were converted to the mzML format using ProteoWizard, and processed by R package xcms (ver.…”
Section: Methodsmentioning
confidence: 99%
“…After homogenization for three times, it was incubated for 1 h at À20°C to precipitate proteins and then centrifuged at 17 000 g for 15 min at 4°C to get the resulting supernatants. LC-MS/MS analyses (Wang et al 2016) were performed using an UHPLC system (1290; Agilent Technologies, Palo Alto, CA, USA) with a UPLC HSS T3 column (1Á7 lm 9 2Á1 mm 9 100 mm; Waters, Milford, MA, USA) coupled to Q Exactive (Orbitrap MS; Thermo, Waltham, MA, USA). MS raw data (.d) files were converted to the mzML format using ProteoWizard, and processed by R package XCMS (ver.…”
Section: Fatty Acid Extraction and Uplc-ms Analysismentioning
confidence: 99%